(untitled) (Филолошки студии, 2019)
In the essay the author analyzes some aspects of the mutual perceptions of Russian and Macedonian cultures. The short survey of the most important current achievements of Russian translators from Macedonian and vice versa is given. The author speculates on possibilities and difficulties of entering Macedonian Literature Russian literary and cultural contexts and on inevitable rapprochement of the two Slav cultures and stresses the importance of such a process in the term of globalization, when there is a risk for Slav nations to loose their identities. Translators’ activities are to play a very notable role in this respect and in the process of strengthening inter-Slav ties.